Outcome of COVID-19 in allogeneic stem cell transplant recipients: Results from the EPICOVIDEHA registry - Alessandro Busca; Jon Salmanton-García; Jon Salmanton-García; Francesco Marchesi; Francesca Farina; Guldane Cengiz Seval; Jaap Van Doesum; Nick De Jonge; Nathan C. Bahr; Johan Maertens; Johan Maertens; Joseph Meletiadis; et al. (Frontiers in Immunology, 2023)
BackgroundThe outcome of COVID-19 in allogeneic hematopoietic stem cell transplantation (HSCT) recipients is almost uniformely considered poor. The aim of present study was to retrospectively analyse the outcome and risk factors for mortality in a large series of patients who developed COVID-19 infection after an allogeneic HSCT.MethodsThis multicenter retrospective study promoted by the European Hematology Association – Infections in Hematology Study Working Group, included 326 adult HSCT patients who had COVID-19 between January 2020 and March 2022.ResultsThe median time from HSCT to the diagnosis of COVID-19 was 268 days (IQR 86-713; range 0-185 days). COVID-19 severity was mild in 21% of the patients, severe in 39% and critical in 16% of the patients. In multivariable analysis factors associated with a higher risk of mortality were, age above 50 years, presence of 3 or more comorbidities, active hematologic disease at time of COVID-19 infection, development of COVID-19 within 12 months of HSCT, and severe/critical infections. Overall mortality rate was 21% (n=68): COVID-19 was the main or secondary cause of death in 16% of the patients (n=53).ConclusionsMortality in HSCT recipients who develop COVID-19 is high and largely dependent on age, comorbidities, active hematologic disease, timing from transplant and severity of the infection.